Marine Sponges as Chloroflexi Hot Spots: Genomic Insights and High-Resolution Visualization of an Abundant and Diverse Symbiotic Clade - Bayer, Kristina (mSystems, 2018)
Members of the widespread bacterial phylum Chloroflexi can dominate high-microbial-abundance (HMA) sponge microbiomes. In the Sponge Microbiome Project, Chloroflexi sequences amounted to 20 to 30% of the total microbiome of certain HMA sponge genera with the classes/clades SAR202, Caldilineae, and Anaerolineae being the most prominent. We performed metagenomic and single-cell genomic analyses to elucidate the functional gene repertoire of Chloroflexi symbionts of Aplysina aerophoba. Eighteen draft genomes were reconstructed and placed into phylogenetic context of which six were investigated in detail. Common genomic features of Chloroflexi sponge symbionts were related to central energy and carbon converting pathways, amino acid and fatty acid metabolism, and respiration. Clade-specific metabolic features included a massively expanded genomic repertoire for carbohydrate degradation in Anaerolineae and Caldilineae genomes, but only amino acid utilization by SAR202. While Anaerolineae and Caldilineae import cofactors and vitamins, SAR202 genomes harbor genes encoding components involved in cofactor biosynthesis. A number of features relevant to symbiosis were further identified, including CRISPR-Cas systems, eukaryote-like repeat proteins, and secondary metabolite gene clusters. Chloroflexi symbionts were visualized in the sponge extracellular matrix at ultrastructural resolution by the fluorescence in situ hybridization-correlative light and electron microscopy (FISH-CLEM) method. Carbohydrate degradation potential was reported previously for “Candidatus Poribacteria” and SAUL, typical symbionts of HMA sponges, and we propose here that HMA sponge symbionts collectively engage in degradation of dissolved organic matter, both labile and recalcitrant. Thus, sponge microbes may not only provide nutrients to the sponge host, but they may also contribute to dissolved organic matter (DOM) recycling and primary productivity in reef ecosystems via a pathway termed the sponge loop. IMPORTANCE Chloroflexi represent a widespread, yet enigmatic bacterial phylum with few cultivated members. We used metagenomic and single-cell genomic approaches to characterize the functional gene repertoire of Chloroflexi symbionts in marine sponges. The results of this study suggest clade-specific metabolic specialization and that Chloroflexi symbionts have the genomic potential for dissolved organic matter (DOM) degradation from seawater. Considering the abundance and dominance of sponges in many benthic environments, we predict that the role of sponge symbionts in biogeochemical cycles is larger than previously thought.